Village Program Strategy in Minimizing the Negative Impact of Online Gambling Influenced by Influencers on Mental Health and Finances in Simpang Empat Village - Fauzi, Said Ihsan; Syahriza, Rahmi; Suhairi, Suhairi (Electronic Journal of Education, Social Economics and Technology, 2025)
Online gambling, influenced by social media influencers, has become a serious problem in many rural communities such as Simpang Empat Village. The impact of this gambling activity is not only limited to the economic aspect but is also significant in affecting the mental health of village residents. This research aims to identify program strategies that can be used by village governments to minimize the negative impacts of online gambling. The research method used was in-depth interviews with community leaders, village residents who were directly affected, and also social observers. Data was analyzed using a qualitative approach to describe different views and experiences regarding online gambling and the influence of influencers. The results highlight the importance of collaboration between village governments, and communities in developing sustainable solutions to combat online gambling and raise awareness of the risks associated with this activity. Online gambling has become a significant problem in many communities, including villages, with widespread economic and psychological impacts. It is hoped that this research can contribute to developing sustainable policies and intervention strategies to reduce the prevalence of online gambling and mitigate its impact on the mental health and finances of rural communities. By implementing appropriate program strategies, it is hoped that we will be able to create a safer and more supportive environment for economic development and mental well-being in Simpang Empat Village.